The governance of the international monetary system - José Antonio Ocampo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper proposes a reformed architecture of the international monetary system based on three pillars. The first is a representative apex organization, which can be understood as a transformation of the G-20 into a representative international institution. The second is the continuous reform of 'voice and participation' of developing countries in the Bretton Woods Institutions and global regulatory bodies. The third is the design of a 'dense', multi-layered architecture, with the active contribution of regional and sub-regional institutions, in a sense copying in this regard the denser architecture in place in the system of multilateral development banks.
Keywords: F02; F33; 330; International Monetary Fund; Group of 20; IMF quotas and votes; regional financial institutions